(untitled) (Web of Technology: Multidimensional Research Journal, 2026)
This article addresses the issues of improving the reliability of wall structures in seismic-resistant frame buildings. The study analyzes structural solutions of infill walls, material selection, and their energy dissipation properties in ensuring the seismic stability of building structures. In addition, modern strengthening technologies, innovative construction materials, and computational models are considered as means to enhance the earthquake resistance of wall elements. The research results contribute to increasing the safety and stability of frame buildings.